Comparison between two age-structured models, applied to the lobster fishery, Panulirus argus (Latreille, 1804), in the southeastern region of Cuba - Alzugaray-Martínez, Romina (2012)
Spiny lobster, Panulirus argus, is one of the most commercially valuable species in the Western Central Atlantic. Although numerous studies have been conducted in Cuba to learn and update its exploitation status and to recommend management measures, catches continue to decline. Consequently, the objective of this study was to evaluate the dynamics of the lobster population in Cuba’s southeastern region, through two different analytical strategies. Using catch and fishing effort data from 1979-2010, a Virtual Population Analysis (VPA) and a Statistical Catch-at-age Analysis (SCA) were applied. We examined the linear relationship between raw data and the variables estimated by the models. The fit of the linear models to data was assessed using the corrected Akaike Information Criterion (AICc). According to both age-structured methods, population size and recruitment of one year old lobster have declined in the region during the study period, although the SCA shows stabilization in the last decade. Population biomass decreased to stabilize in the last decade, this may relate to the historical behavior of the catch per unit effort. There are significant linear associations between raw data and estimated variables. According to Δi values, the VPA model ensures the best fit for the variables of estimated linear relationships.